THE TECHNIQUE OF IMPROVING THE SPEAKING SKILL USING MUSIC CASE STUDY AT ANALIS KESEHATAN MUHAMMADIYAH MAKASSAR - Fitri Arniati (Jurnal Medika, 2016)
There are some factors that cause of low levels of student skills, internal and external factors. External factors including the use of indonesian influence in family environment and society even in everyday communication. Therefore, To guide the students speak in english in the classroom lecturer should have good and interesting technique of teaching. Using music in the classroom can immerge students to be involved actively and able to express orally their idea, do collectively, and communicative. This research aims to finding out whether use of music can improve the speaking skill students at the first year of Analis Kesehatan Muhammadiyah Makassar. The results show students speaking ability improve than before using this technique and reduce difficulties faced by students.